El Género y la inserción laboral de los profesionales de la Carrera de Economía de la Universidad Nacional de Chimborazo en el período 2010-2016. - Castillo Alcoser, Bethsy Gabriela (2018)
The present investigation work: "The gender and the labor insertion of the professionals of the Career of Economy of the National University of Chimborazo, in the period 2010-2016"; analyzes the incidence that exists between the explanatory variable called gender and the explained that is the Labor Insertion; process in which it is demonstrated through tables and graphs statistics as is the performance of the different indicators in the study period; it is also necessary to emphasize that due to the behavior of the variables these are hold to the Multivariate Binary Logistic Regression Model with the application of a Logit Model. The structure of this work is presented by chapters that are organized as follows: in Chapter I, will be found everything concerning the Reference Framework; Chapter II, will be focused on the Theoretical Framework and it incluide definitions, differences of terms and theoretical approaches with respect to gender, while in reference to labor insertion, enumerate determinants and impact factors. Chapter III, is formed of the Methodological Framework, where is enunciated the methodology applied in this study, the analysis and discussion of data is based on the measurement instrument of the surveys and as the last point will be the analysis of results that is done with the execution of the Econometric Model, with the use of the statistical package SPPS 23.0. Finally, Chapter IV, include the conclusions and recommendations that were reached after the research process, which may be the basis for future research.